2012
DOI: 10.1128/aem.06410-11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anaerobiosis and Low Temperature on Bacillus cereus Growth, Metabolism, and Membrane Properties

Abstract: The impact of simultaneous anaerobiosis and low temperature on growth parameters, metabolism, and membrane properties of Bacillus cereus ATCC 14579 was studied. No growth was observed under anaerobiosis at 12°C. In bioreactors, growth rates and biomass production were drastically reduced by simultaneous anaerobiosis and low temperature (15°C). The two conditions had a synergistic effect on biomass reduction. In anaerobic cultures, fermentative metabolism was modified by low temperature, with a marked reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 49 publications
10
47
0
Order By: Relevance
“…Therefore, in the present investigation, we opt for optimization of mass production of the selected strain. Results of this study are consistent with those of previous studies, where the culture media had a significant influence on production of B. cereus (De Sarrau et al 2012, Singh et al 2013. Singh et al (2013) used response …”
Section: Optimization Of Biomass Production By Rsmsupporting
confidence: 83%
“…Therefore, in the present investigation, we opt for optimization of mass production of the selected strain. Results of this study are consistent with those of previous studies, where the culture media had a significant influence on production of B. cereus (De Sarrau et al 2012, Singh et al 2013. Singh et al (2013) used response …”
Section: Optimization Of Biomass Production By Rsmsupporting
confidence: 83%
“…We also report the functional characterization of the enzymes involved in this process. It was previously shown that B. cereus grown in different media and at different temperatures synthesized UFAs with double bonds in different positions in membrane lipids (11,12,28). In the present study, we established that in a minimal defined medium devoid of FAs, B. cereus synthesizes ⌬5, ⌬10, and ⌬5,10 UFAs.…”
Section: Discussionmentioning
confidence: 53%
“…Some psychrophilic species of Bacillus as well as B. cereus have an unusually high proportion of UFAs (8,9). Two recent studies on B. cereus strains showed that the adaptation of the membrane lipid composition of cells grown aerobically and isothermally at low temperatures was principally associated with a large increase in the proportion of UFAs (10,11). B. cereus species contain a high proportion of ⌬10 UFAs in their membrane lipids at 37°C, while at low temperatures they synthesize both ⌬10 and ⌬5 isomers (12).…”
mentioning
confidence: 99%
“…For instance, membrane fatty acid (FA) composition adjustments can increase the proportion of low-meltingpoint FAs (like unsaturated FAs and branched-chain FAs) (8)(9)(10). RNA helicases that enable the RNA unfolding needed for proper translation and/or RNA degradation also play a major role in B. cereus low-temperature adaptation (11).…”
mentioning
confidence: 99%